2023
DOI: 10.1186/s10020-023-00689-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of microbial colonization in the premature gut

Abstract: Abnormal microbial colonization in the gut at an early stage of life affects growth, development, and health, resulting in short- and long-term adverse effects. Microbial colonization patterns of preterm infants differ from those of full-term infants in that preterm babies and their mothers have more complicated prenatal and postnatal medical conditions. Maternal complications, antibiotic exposure, delivery mode, feeding type, and the use of probiotics may significantly shape the gut microbiota of preterm infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 176 publications
(234 reference statements)
0
2
0
Order By: Relevance
“…During a vaginal birth, neonates traverse the birth canal, encountering a diverse array of maternal microorganisms that confer an early inoculation of the infant's gut [58][59][60].…”
Section: Mechanisms Involvedmentioning
confidence: 99%
“…During a vaginal birth, neonates traverse the birth canal, encountering a diverse array of maternal microorganisms that confer an early inoculation of the infant's gut [58][59][60].…”
Section: Mechanisms Involvedmentioning
confidence: 99%
“…Nuntnarumit et al reported [ 14 ] that CRP is indicative for the diagnosis of EOS, leading to prolonged antibiotic use in neonatal intensive care units (NICUs) usually due to high CRP status. This inevitably leads to overuse of antibiotics, resulting in the development and spread of antibiotic resistance [ 15 ] and other adverse outcomes such as neonatal necrotizing enterocolitis (NEC) and late-onset sepsis (LOS) [ 16 ]. And excessive antibiotic therapy increases the risk of abnormal bacterial colonization, increase in resistant bacteria, and allergic manifestations [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This inevitably leads to overuse of antibiotics, resulting in the development and spread of antibiotic resistance [ 15 ] and other adverse outcomes such as neonatal necrotizing enterocolitis (NEC) and late-onset sepsis (LOS) [ 16 ]. And excessive antibiotic therapy increases the risk of abnormal bacterial colonization, increase in resistant bacteria, and allergic manifestations [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%